ANCIENT TAXATION SYSTEMS (International journal of artificial intelligence, 2025)
Taxation has been a critical part of governance since the earliest civilizations, making sure nation sales for infrastructure, army, and administration. Historic societies developed numerous taxation structures, regularly tailor-made to their economies and political structures.In historical Egypt, taxation became based totally on agriculture, with farmers paying in grain and labor. The pharaohs also imposed pressured the population to pay one-5th of their harvested crops as a tax. Similarly, Mesopotamian rulers taxed vegetation, cattle, and trade, with strict enforcement recorded in felony codes like Hammurabi’s.Those early taxation systems encouraged modern-day monetary policies, demonstrating how governments have lengthy depended on taxes to preserve economies and manipulate societies. Knowledge historical taxation gives insight into the historic balance between state energy and financial obligation. The paper concludes with proposals for fostering a tax structure this is each proficient and sustainable, that can assist governments in reaching financial stability.